DIPG-45. RADIATION DOSE RESPONSE OF NEUROLOGIC SYMPTOM IMPROVEMENT DURING RADIOTHERAPY FOR DIFFUSE INTRINSIC PONTINE GLIOMA. Issue 2 (22nd June 2018) - Tinkle, Christopher; Campbell, Kristen; Bianski, Brandon; Li, Yimei; Han, Yuanyuan; Broniscer, Alberto; Sadghi, Zsila; Merchant, Thomas
Abstract: PURPOSE: To investigate the association between radiation dose response and neurologic symptom improvement and survival outcomes in patients with diffuse intrinsic pontine glioma (DIPG). METHODS AND MATERIALS: 108 patients with newly-diagnosed DIPG were treated with conventionally-fractionated radiation therapy (RT) to 54Gy (median) at our institution from 2006 to 2014. The presence and severity of neurological symptoms related to cranial neuropathy (CN) and cerebellar (CB) and long tract (LT) signs prior to and weekly during RT was reviewed for each patient. The incidence and rate of change of each symptom category was evaluated to determine the impact of clinical variables and brain sub-region volumes using Cox proportional hazard models. RESULTS: Median dose to first sign of symptomatic improvement was 16.2Gy (CN), 21.6Gy (CB) and 19.8Gy (LT). Most patients showed any improvement by 20Gy. Black race was associated with improved LT signs at significantly lower cumulative RT doses (P=0.027). Larger uninvolved brainstem volume alone and normalized to total brain (TB) or posterior fossa volume (PF) was associated with a shorter time to LT sign improvement (P=0.044, P=0.033, and P=0.05, respectively). Patients with any improvement in CN experienced significantly prolonged progression-free (PFS) and overall survival (OS) (P=0.002 and P=0.008, respectively). Tumor volume, with or without normalization to TB or PF, was not significantly associated with PFS or OS. CONCLUSIONS: Low cumulative doses of RT provided neurologic improvement in the majority of patients with DIPG. Brain sub-region volumes influenced time to symptomatic improvement, while neurologic improvement was associated with superior survival outcomes.